2022
DOI: 10.1002/hbm.25949
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive enhancement: Effects of methylphenidate, modafinil, and caffeine on latent memory and resting state functional connectivity in healthy adults

Abstract: Stimulants like methylphenidate, modafinil, and caffeine have repeatedly shown to enhance cognitive processes such as attention and memory. However, brain‐functional mechanisms underlying such cognitive enhancing effects of stimulants are still poorly characterized. Here, we utilized behavioral and resting‐state fMRI data from a double‐blind randomized placebocontrolled study of methylphenidate, modafinil, and caffeine in 48 healthy male adults. The results show that performance in different memory tasks is en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 116 publications
1
8
0
3
Order By: Relevance
“…Por fim, outras pesquisas são necessárias para investigar os efeitos induzidos por estimulantes compartilhados em diferentes sistemas de neurotransmissores, como as catecolaminas (dopamina), que dão origem a essas mudanças de rede neural em grande escala. Além disso, precisa ser reafirmado que os psicoestimulantes sob prescrição médica só possuem evidências para serem prescritos em caso de patologias específicas (Becker et al, 2022).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por fim, outras pesquisas são necessárias para investigar os efeitos induzidos por estimulantes compartilhados em diferentes sistemas de neurotransmissores, como as catecolaminas (dopamina), que dão origem a essas mudanças de rede neural em grande escala. Além disso, precisa ser reafirmado que os psicoestimulantes sob prescrição médica só possuem evidências para serem prescritos em caso de patologias específicas (Becker et al, 2022).…”
Section: Discussionunclassified
“…A diminuição da conectividade negativa entre o pré-frontal direito e o parietal medial, mas também entre o lobo temporal medial e as regiões visuais do cérebro, previu o aumento da memória Research, Society andDevelopment, v. 12, n. 2, e10512239958, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i2.39958 latente induzida por estimulantes. Assim, os resultados preliminares indicam que a redução da FC negativa entre o FPN e DMN, bem como entre as regiões visual, reflete um efeito de aprimoramento cognitivo no nível do sistema neural específico para o aprimoramento de memória induzido por estimulantes (Becker et al, 2022).…”
Section: Ilieva Et Al 2013unclassified
“…shown that abnormal right frontoparietal network activity might be closely related to impaired working memory and attention deficits (Becker et al, 2022;Chen et al, 2023;Letkiewicz et al, 2022;May & Kana, 2020;Tan et al, 2021;Yuk et al, 2020;Zhou et al, 2023).…”
Section: Agementioning
confidence: 99%
“…39 Further, the DA reuptake inhibitors, methylphenidate and modafinil have been used to treat PSF. 12,40,41 Methylphenidate reportedly reduces fatigue in small studies of chronic fatigue, 41 Multiple Sclerosis, Parkinson's disease, and cancer. 39,42 There is evidence that methylphenidate reduces the cost of mental labor (ie, perceived effort).…”
Section: Precipitating Factors Of Psfmentioning
confidence: 99%
“…67,68 Exercise may ameliorate some of the peripheral (aerobic deconditioning and muscle atrophy) and central disturbances (alterations in cerebral blood flow, cellular energy stores, and neural circuit activity) that potentially contribute to PSF. 36-71 In a small RCT using a combination of 12-weeks of cognitive training and exercise, addition of exercise reduced fatigue compared to control subjects that received cognitive training alone. 16 A recent systematic review explored whether exercise impacts fatigue using the FSS.…”
Section: Exercise As a Possible Intervention For Psfmentioning
confidence: 99%